Penggunaan Klinometer sebagai Pendukung Penguatan Konsep Siswa tentang Perbandingan Trigonometri - Syahrudi Syahrudi (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2019)
The basic concept of trigonometric ratios now is not excellently grasped by students of Granada Islamic Senior Secondary School. The problem identification result shows that there is students’ ennui due to the indoors mathematics learning. This study aims to reinforce basic concepts of trigonometric ratios by increasing the students’ learning activities and mastery kearning by means of clinometer. The benefits of this study are (1) for mathematics teachers, it is an effort to elaborate science by utilising clinometer in teaching and learning and (2) as for students, it is to enable them applying trigonometry in daily life. Clinometer is one of the simple teaching aids used to measure the height of an object utilizing elevation angles and trigonometric ratios. The tests result and observational record shows that students’ activities increase from 39.39% to 93.93% as well as students' mastery learning that increases from 25% to 84.84%. The result of this study indicates that the use of clinometer may support the students' concepts reinforcement on trigonometric ratios.